Gastro-gastric fistula following gastric bypass: a case report - Arango Molano, Lázaro Antonio (2025)
A gastro-gastric fistula is an abnormal communication between the excluded gastric pouch and the gastric remnant following Roux-en-Y gastric bypass surgery. This complication typically arises in the late postoperative period and occurs in fewer than 1% of patients. Diagnosing a gastro-gastric fistula can be clinically challenging, as it may present with a spectrum ranging from asymptomatic states to nonspecific symptoms such as epigastric pain, weight regain, gastroesophageal reflux, and emesis. A combination of endoscopic evaluation and contrast imaging studies is essential to establish a diagnosis. There is currently no optimal standardized treatment strategy. Conservative management is generally reserved for asymptomatic patients. Surgical correction remains the standard approach; however, it is technically demanding and associated with higher morbidity compared to primary bariatric procedures. Consequently, novel endoscopic techniques and approaches have emerged, demonstrating promising outcomes and safety profiles in the management of gastro-gastric fistulas.